2008
DOI: 10.17660/actahortic.2008.801.143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Biofertiliser on the Growth of Poinsettia

Abstract: The experiment was aimed to evaluate the effect of a biofertiliser containing the purple nonsulfur anoxygenic phototrophic bacterium Rhodobacter capsulatus (Ores, PSBIO System, Italy) on the growth of two poinsettia cultivars, 'Peterstar' and 'Maren', in comparison with the usual nitrogen fertigation. The plants were grown in a PMMA covered greenhouse, in 18 cm diameter pots filled with a peat based commercial substrate. Five treatments were compared: 1) the untreated control; 2) 120 mg N as NH 4 NO 3 per pot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
3
0
0
Order By: Relevance
“…In terms of dry weight of plant, the effect of the applications was not significant (p>0.05) according to in 2 nd year and general averages of the data for the two years of the study (Table 2). Our study results related to the dry weight of plant increase are in harmony with of the results of researches studied by Kokalis-Burelle et al (2002) (for tomato and pepper seedling), Jaleel et al (2007) (for Madagascar periwinkle), Martinetti et al (2007) and Thapa (2017) (for poinsettia).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of dry weight of plant, the effect of the applications was not significant (p>0.05) according to in 2 nd year and general averages of the data for the two years of the study (Table 2). Our study results related to the dry weight of plant increase are in harmony with of the results of researches studied by Kokalis-Burelle et al (2002) (for tomato and pepper seedling), Jaleel et al (2007) (for Madagascar periwinkle), Martinetti et al (2007) and Thapa (2017) (for poinsettia).…”
Section: Resultssupporting
confidence: 92%
“…Jaleel et al (2007) demonstrated that Pseudomonas fluorescens has positive effects on fresh weight of Madagascar periwinkle (Catharanthus roseus). Our study results related to the fresh weight of plant increase are in harmony with of the results of researches studied by Jaleel et al (2007), Martinetti et al (2007) and Ge et al (2016). In the first year of the study, applications on the dry weight of plant were statistically significant at p<0.05 level.…”
Section: Resultssupporting
confidence: 88%
“…The above mentioned results are in harmony with those obtained by Jaleel et al [38] and Eid et al, [37]. Martinetti et al [39] reported that the plant weight ranged from 2.03 to 2.85 g. It can be said that dry weight of poinsettia plants increased in the present study when compared the results of study conducted by Martinetti et al [39].…”
Section: Plant Parameterssupporting
confidence: 91%